Avaliação económica de Fidaxomicina no tratamento de infeções por Clostridium difficile graves ou recorrentes - Gouveia, Miguel (2013)
Objectives: Fidaxomicin is a macrocyclic antibiotic drug indicated for the treatment of Clostridium difficile infections (CDI). The purpose of this study was to evaluate from a societal perspective the cost-effectiveness and cost-utility of fidaxomicin in the treatment of severe or recurrent CDI compared to the recommended alternative therapy, vancomycin. Methods: The effectiveness estimates of fidaxomicin and vancomycin, provided by two clinical trials in addition to other studies, were extrapolated to 10 days cycles and a time horizon of 1 year using a Markov model. The costs considered in the study included medication, hospitalization, complications and outpatient visits. Estimates of the indirect costs generated by productivity losses due to absenteeism were not included, for lack of relevant evidence for the Portuguese reality and because the population affected by CDI tends to be no longer active in the labor market. Results: Over a one year horizon and compared to vancomycin treatment, in the base case, fidaxomicin treatment in patients with severe ICD is associated with a gain of 0.010 QALY and a cost increase of 138 €. The treatment of patients with recurrent CDI with fidaxomicin is associated with a gain of 0.019 QALYs and a cost reduction of 626 €. Fidaxomicin treatment has an acceptable incremental cost-utility ratio in patients with severe CDI (ICUR: 13,245 €/ QALY) and dominates in patients with recurrent CDI (ICUR: -33,701 €/ QALY). Fidaxomicin treatment in patients with severe and recurrent CDI is also associated with a reduction in the number of recurrences (ICER: 321 €/ recurrence avoided in patients with severe CDI and ICER: -828 €/ recurrence avoided in patients with recurrent CDI). These results are sensitive to the cost of hospitalization, decreasing with a rising cost of hospitalization. In the probabilistic sensitivity analysis the model predicts that the probability of cost-effectiveness of fidaxomicin is 44,9% in the case of severe CDI and 58% for recurrent CDI for a willingness to pay threshold of 30.000 €. Conclusions: In the Portuguese health system context, fidaxomicin presents good cost-effectiveness and cost-utility results, representing a valuable addition to the therapeutic arsenal for the treatment of CDI.